1987
DOI: 10.1063/1.338264
|View full text |Cite
|
Sign up to set email alerts
|

Gettering of gold in silicon: A tool for understanding the properties of silicon interstitials

Abstract: The movement of gold in silicon is controlled by the reaction of gold with silicon interstitials, not by the intrinsic diffusion coefficient of gold. This fact is used to understand the role silicon interstitials play during gettering in silicon. An analysis of gold profiles after gettering reveals that high concentration phosphorus diffusion, argon-ion implantation, and mechanical damage of a silicon surface all act as sources of silicon interstitials. This finding is experimentally confirmed by studying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
6

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(38 citation statements)
references
References 23 publications
0
30
0
6
Order By: Relevance
“…Bronner and Plummer (1985) showed that layers damaged by high-dose argon implantation inject point defects for long periods of time. Later experiments by Bronner and Plummer (1987) confirmed that interstitial injection was the dominant process when they observed no antimony enhancement, which would occur during vacancy injection. Both of these surface treatments are also efFective gettering techniques.…”
Section: Determining the Point-defect Parametersmentioning
confidence: 53%
See 2 more Smart Citations
“…Bronner and Plummer (1985) showed that layers damaged by high-dose argon implantation inject point defects for long periods of time. Later experiments by Bronner and Plummer (1987) confirmed that interstitial injection was the dominant process when they observed no antimony enhancement, which would occur during vacancy injection. Both of these surface treatments are also efFective gettering techniques.…”
Section: Determining the Point-defect Parametersmentioning
confidence: 53%
“…Based on the above similarities and the observation that direct metal diffusion to an infinite sink could not account for the time dependence of gettering profiles, Bronner and Plummer (1987) proposed a causal link between interstitial injection and gold gettering. Under equilibrium conditions, the fraction of gold on substitutional sites is much greater than that on interstitial sites.…”
Section: Determining the Point-defect Parametersmentioning
confidence: 95%
See 1 more Smart Citation
“…Measurements of the diffusion rate of defects in silicon have been reported in experiments. [8][9][10][11][12][13][14] Current experimental techniques cannot cleanly resolve the diffusion rates of more complex defect species, and due to the atomicscale size of point defects, defect diffusion pathways cannot be resolved at all. 15 Thus, numerical simulations provide a unique way to study the technologically important dynamics of point defects in silicon.…”
mentioning
confidence: 99%
“…is the effective diffusivity of Sh. Considering the value given by G. B. Bronner [8] for DIet! at 750°C, [Aus] should be equal to 1.3x1012 cm-3.…”
Section: Contamination Of the Wafersmentioning
confidence: 99%